2011
DOI: 10.1111/j.1365-2133.2011.10338.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aqueous Cream BP on corneocyte size, maturity, skin protease activity, protein content and transepidermal water loss

Abstract: SummaryBackground Aqueous Cream BP is frequently prescribed for patients with eczema and is known to induce sensitivity in certain patients and also to decrease the thickness of the stratum corneum (SC). We have previously reported methodology to quantify corneocyte maturity and size, protease activity and protein content within different levels of the SC. Objectives The aim of the present study was to investigate changes in corneocyte size, corneocyte maturity, selected protease activities, protein content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 30 publications
(73 reference statements)
0
36
0
Order By: Relevance
“…For example, some optimally designed emollients containing humectants ameliorate skin dryness and reduce the severity of skin inflammation [11,12,13]. In stark contrast, aqueous cream, containing the harsh anionic surfactant sodium lauryl sulphate (SLS) and no humectant, was found to damage the skin barrier [14,15,16,17], an effect linked to high rates of adverse reactions and exacerbation of AD symptoms [18]. In response to growing evidence and improvements in emollient formulation, a recent consensus statement by health care professionals highlighted the need to differentiate emollients based on their mechanism of action [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, some optimally designed emollients containing humectants ameliorate skin dryness and reduce the severity of skin inflammation [11,12,13]. In stark contrast, aqueous cream, containing the harsh anionic surfactant sodium lauryl sulphate (SLS) and no humectant, was found to damage the skin barrier [14,15,16,17], an effect linked to high rates of adverse reactions and exacerbation of AD symptoms [18]. In response to growing evidence and improvements in emollient formulation, a recent consensus statement by health care professionals highlighted the need to differentiate emollients based on their mechanism of action [19].…”
Section: Introductionmentioning
confidence: 99%
“…This innate immunity, which further underlies the skin's ability for repairing itself, is crucial for survival. The application of simple emollient formulations has been shown to alter desquamatory and inflammatory enzyme activity in the SC (Mohammed et al, 2011).…”
Section: Current Understanding Of Skin Barrier Functionmentioning
confidence: 99%
“…It usually contains sodium lauryl sulphate (SLS), a known skin irritant. Recent work has shown that application of aqueous cream reduces Stratum corneum thickness and increases the rate of trans-epidermal water loss (TEWL) during tape stripping [ 31 ] and is associated with reduced maturity and size of corneocytes and increased desquamatory and infl ammatory protease activity [ 32 ] .…”
Section: Harmful Effects Ofmentioning
confidence: 99%